I haven't been entirely honest with you - Hart, Miranda 1972- (Penguin Michael Joseph, 2024)
"Packed with hard-won wisdoms and gentle truths, this is Miranda's honest exploration of the lessons she has learned on her journey from illness to recovery"--Provided by publisher
Keywords: Hart, Miranda -- 1972-; Hart, Miranda / 1972-; Well-being; Mental illness / Treatment; Bien-être; Maladies mentales / Traitement; comfort (sensation); Self-help publications; Livres de croissance personnelle; Autobiografie